Co9S8–carbon composite as anode materials with improved Na-storage performance. (November 2015) - Ko, You Na; Kang, Yun Chan
Abstract: The synthesis and electrochemical performance of a composite of Co9 S8 nanoparticles and amorphous carbon is studied as an anode material for sodium-ion batteries. The Co9 S8 –carbon composite powder was fabricated through a one-pot spray pyrolysis process using thiourea and polyvinylpyrrolidone as sulfur and carbon sources, respectively. The Co9 S8 nanoparticles are entirely covered by an amorphous carbon layer. The initial discharge and charge capacities of the Co9 S8 –carbon composite powder were 689 and 475 mA h g −1, respectively, at a current density of 0.5 A g −1 . The Co9 S8 –carbon composite powders exhibited a stable cyclability with a reversible capacity of 404 mA h g −1 for the 50th cycle and a superior rate capability compared with bare Co1− x S powder. The improvement of Na-storage performance could be attributed to the small size and entanglement of the Co9 S8 nanoparticles within the carbon matrix.